Effect of Diazonium Salt and Aluminum Oxide on Microleakage of PMMA at Co/Cr and Titanium Alloys Interface (Mustansiria Dental Journal, 2024)
Aim of the study: The junction between metal alloy and acrylic resin is an area of clinical concern, failure of removable partial denture may relate to this interface. The purpose of this study was to evaluate the effect of different surface treatments (diazonium salt and aluminum oxide) on microleakage of heat cure acrylic resin at the Co/Cr and titanium alloys interface.Materials and method: Sixty rectangular-shaped specimens divided into 2 main groups, 30 specimens for Co/Cr alloy and 30 specimens for titanium alloy, then subdivided into 3 groups each one consist of 10 specimens, according to the type of surface treatments. Aluminum oxide group abraded with (Al2O3) ll0 μm and diazonium salt group treated based on two steps, first step (primer) and second step (adhesive). Chemical composition of diazonium salt surface treatment was analyze with (FTIR). All specimens thermocycled in artificial saliva (3000 cycles) after clear heat cured acrylic resin application, then immersed in sodium fluorescein dye solution (0.1 g/1000mL) for 24 hours at room temperature. Microleakage was assessed by counting the grids that exhibited dye penetration under ultraviolet light. Data analyzed via One-way ANOVA and LSD test.Results: Microleakage test showed a significant decrease in mean value between PMMA and treated Co/Cr or titanium with diazonium salt by 1.90 and 2.00 respectively (p